2015
DOI: 10.1007/s00223-015-0033-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Osteoporosis in Relation to Muscle Mass

Abstract: This study aimed to examine the relationship between metabolic syndrome (MetS) and osteoporosis according to muscle mass levels and the joint relationship of MetS and muscle mass with osteoporosis in a representative population-based sample from the Korea National Health and Nutrition Examination Survey in 2010-2011. In 1654 men and 1979 women aged 50-93 years, body composition and bone mineral density at the femur and lumbar spine were measured using dual-energy X-ray absorptiometry. Low- and high-muscle mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Applying this method led to the second main finding of this study: the ORs of having the MetS increased in younger and older men and women with larger FFMi, independently of multiple covariables. Although it opposes the widespread belief that FFM has a protective effect on metabolic health, this conclusion is in line with previous counterintuitive observations from multiple published studies 4,15,17,18,20,23,24,28–31 . The authors of these studies, however, have not always put forward, if discussed, their results.…”
Section: Discussionsupporting
confidence: 62%
“…Applying this method led to the second main finding of this study: the ORs of having the MetS increased in younger and older men and women with larger FFMi, independently of multiple covariables. Although it opposes the widespread belief that FFM has a protective effect on metabolic health, this conclusion is in line with previous counterintuitive observations from multiple published studies 4,15,17,18,20,23,24,28–31 . The authors of these studies, however, have not always put forward, if discussed, their results.…”
Section: Discussionsupporting
confidence: 62%
“…There was a significant relationship between muscle mass and MetS and prevalence of osteoporosis among Koreans (1654 men and 1979 women, aged 50–93 years). Body composition and BMD were determined using dual-energy X-ray absorptiometry (DEXA) and findings showed that higher muscle mass and MetS were associated with a lower prevalence of osteoporosis in men and women (OR 0.65, 95% CI 0.46–0.91) [ 53 ].…”
Section: The Association Between Mets and Osteoporosismentioning
confidence: 99%
“…Recently, there is a debate concerning whether MetS is associated with osteoporosis. Many studies involving animals and humans have been performed to investigate the relationship between MetS and osteoporosis but the findings were heterogeneous [ 9 14 ]. Human observational studies revealed that individual with MetS had either higher [ 9 , 12 ] or lower bone mineral density (BMD) [ 10 , 15 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies involving animals and humans have been performed to investigate the relationship between MetS and osteoporosis but the findings were heterogeneous [ 9 14 ]. Human observational studies revealed that individual with MetS had either higher [ 9 , 12 ] or lower bone mineral density (BMD) [ 10 , 15 – 17 ]. Animal studies also yielded inconsistent results, whereby MetS decreased [ 18 ] or had no effect [ 19 ] on BMD in animals.…”
Section: Introductionmentioning
confidence: 99%